Numerical analysis of the energy-dependent radiative transfer equation. (25th May 2018) - Czuprynski, Kenneth; Eichholz, Joseph; Han, Weimin
Abstract: The energy-dependent form of the radiative transfer equation (RTE) is important in a variety of applications. In a previous paper the well-posedness and an energy discretization for the energy-dependent RTE were investigated. In this paper the fully discrete scheme is introduced and analysed. Optimal-order error estimates and a well-posedness analysis of the discrete system are provided. The theoretical results are validated through numerical examples.